Polarized emission from stretched PPV films viewed at the molecular level. Issue 32 (28th August 2015) - Ramos, Rodrigo; Siqueira, Melissa F.; Cazati, Thiago; Faria, Roberto M.; Caldas, Marilia J.
<x xml:space="preserve">Abstract</x> We present a study on the photoluminescence (PL) of thin films of poly-(p-phenylene vinylene) (PPV), non-stretched and uniaxially stretched.